Competitive Intelligence and Knowledge Creation - Outward insights from an empirical survey - Mourad Oubrich (Journal of Intelligence Studies in Business, 2011)
The 21st century is characterized by many transformations which have had an impact on the growth of companies, such as aggressive competition, layoff plans, terrorist attacks and rising oil prices. It is of importance for a company to develop a protection against future impediments. This can be done by creating knowledge through a competitive intelligence process, which is the main focus of this article. With different theories about knowledge creation and competitive intelligence at hand, a qualitative empirical study was developed. The article presents how a company’s strategic intent, mission and strategic objectives can act as a guide for the competitive intelligence process, in order to gain the information necessary to find opportunities and eliminate threats.